2009
DOI: 10.1002/jnr.22040
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical interaction of an actin‐capping protein, CapZ, with NAP‐22

Abstract: NAP-22 is a neuronal protein localized in the presynaptic membrane and synaptic vesicles and recovered in a Triton-insoluble low-density microdomain fraction after biochemical fractionation of the synaptic plasma membrane. NAP-22 organizes membrane microdomains through binding to membrane lipids such as cholesterol, phosphatidylethanolamine, and phosphatidylinositol 4,5-bisphosphate. In this study, NAP-22-binding proteins were screened through the pull-down assay using brain-derived NAP-22 bound to Sepharose 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…In contrast, and consistent with the fact that BASP1 G2A localizes to the promoter regions of WT1-responsive genes (Figure 3D), we found that anti-WT1 antibodies coimmunoprecipitated both wild-type BASP1 and BASP1 G2A (Figure 4D). The actin-capping protein CapZ was previously shown to bind to BASP1 independently of myristoylation status (Odagaki et al, 2009), and consistent with this we found that CapZ antibodies coimmunoprecipitated both wild-type BASP1 and BASP1 G2A (Figure 4D, lower panel). Taken together, the data in Figure 4D suggest that WT1 interacts with HDAC1 through myristoylation of BASP1 and that BASP1 G2A is specifically defective in interacting with HDAC1.…”
Section: Resultssupporting
confidence: 89%
“…In contrast, and consistent with the fact that BASP1 G2A localizes to the promoter regions of WT1-responsive genes (Figure 3D), we found that anti-WT1 antibodies coimmunoprecipitated both wild-type BASP1 and BASP1 G2A (Figure 4D). The actin-capping protein CapZ was previously shown to bind to BASP1 independently of myristoylation status (Odagaki et al, 2009), and consistent with this we found that CapZ antibodies coimmunoprecipitated both wild-type BASP1 and BASP1 G2A (Figure 4D, lower panel). Taken together, the data in Figure 4D suggest that WT1 interacts with HDAC1 through myristoylation of BASP1 and that BASP1 G2A is specifically defective in interacting with HDAC1.…”
Section: Resultssupporting
confidence: 89%
“…According to the first model, this regulation may be accomplished by their direct interaction with actin or actin-binding proteins (He et al, 1997;Odagaki et al, 2009). The second model presumes that the proteins can bind electrostatically (by means of their basic EDs) and thereby sequester anionic phosphatidylinositol-4,5-diphosphate (PIP 2 ) in the inner leaflet of the plasma membrane Wang et al, 2002;Epand et al, 2004;Tong et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Addition of CHL to the mixture of C-NAP-22 and PS showed little effect on the mobility of NAP-22 in CN-PAGE (data not shown) and electron microscopic observation of Tritontreated NAP-22/PS/CHL complex showed no clear image, molecular background of the Triton-insolubility of the complex is unclear at present. Since, many proteins are known to interact with acidic phospholipids, studies of the effect of NAP-22 on these proteins through the binding to acidic phospholipids will be important to understand the molecular interactions at the inner leaflet of raft [11,13,15,19,20,22].…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol distribution and the localization of this protein were hence considered intimately related [10]. In order to elucidate additional functions of NAP-22, a screening of NAP-22-binding proteins was performed using NAP-22-coupled Sepharose beads and several proteins such as an actin binding protein (CapZ␣) [15], synaptojanin [21], and glutamate decarboxylase (GAD) [12] were identified. Other functions of NAP-22 in transcriptional regulation, apoptosis, and ion channel formation were also reported by other groups [3,16,17].…”
Section: Introductionmentioning
confidence: 99%